-(x+3)+4x=6

Simple and best practice solution for -(x+3)+4x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+3)+4x=6 equation:



-(x+3)+4x=6
We move all terms to the left:
-(x+3)+4x-(6)=0
We add all the numbers together, and all the variables
4x-(x+3)-6=0
We get rid of parentheses
4x-x-3-6=0
We add all the numbers together, and all the variables
3x-9=0
We move all terms containing x to the left, all other terms to the right
3x=9
x=9/3
x=3

See similar equations:

| n+(n+1)+(n+2)+(n+3)+(n+4)=55 | | 10+7.5n=8+7.9n | | 128=k-39 | | h+94=891 | | (2x+7)=65 | | v+9-48=1 | | h+94=894 | | –17+15z=13z+19 | | 2n+8=60 | | 459=27g | | n+(n+1)+(2(n+2)+2(n+3)+55)=3(n+4) | | 634=p+551 | | H=210+33x | | 162+24.50x=4.25 | | -x2+2x=3 | | 4c+2c=4 | | 70x-60=-20x-42 | | r-705=-325 | | -2x/3-3=3 | | w+-66=-95 | | 10w=-8-8w | | 3x(1-x)+12=-3x(x-3) | | -9(5-2)=4(t-15) | | n+(n+1)+2((n+2)+(n+3)+55)=3(n+4) | | 1.19+2f=7.39 | | c+386=831 | | -2(x-4)+6=-4x-4 | | 300/24=18/x | | d+48=64 | | -1-(-18)=x/11 | | 7.2=2w+1.2 | | b-29=179 |

Equations solver categories